The nonlinear impact of government consumption expenditure on economic growth: Evidence from low and low-middle income countries - Mehdi Hajamini; Mohammad Ali Falahi (Cogent Economics & Finance, 2014)
The purpose of this paper is to investigate the impact of government consumption expenditure as a share of GDP on economic growth in developing countries. The paper uses threshold panel model to examine nonlinear relationship between the government consumption expenditure share and economic growth in 21 low-income countries and 11 low-middle income countries during 1981-2007. The results confirm nonlinear relationship, in which the threshold share of government consumption expenditure for the low and low-middle income countries is 16.2 and 16.9% with the confidence intervals of [13.7-17.3%] and [16.5-16.9%], respectively. The results indicate that, after passing the threshold, the effect of government consumption expenditure share on economic growth changes from insignificantly positive to significantly negative.
Keywords: C33; O50; 330; economic growth; government consumption expenditure; threshold panel approach